Reconciling Bagehot with the Fed's response to September 11 - Antoine Martin (Federal Reserve Bank of New York, 2005)
The nineteenth-century economist Walter Bagehot maintained that in order to prevent bank panics, a central bank should provide liquidity at a very high rate of interest. However, most of the theoretical literature on liquidity provision suggests that central banks should lend at an interest rate of zero. This latter recommendation is broadly consistent with the Federal Reserve's behavior in the days following September 11, 2001. This paper shows that Bagehot's recommendation can be reconciled with the Fed's policy if one recognizes that Bagehot had in mind a commodity money regime in which the amount of reserves available is limited. A high price for this liquidity allows banks that need it most to self-select. To the contrary, the Fed has a virtually unlimited ability to temporarily expand the money supply so that self-selection is unnecessary.
Keywords: E4; E5; G2; 330; liquidity provision; lender of last resort; Bagehot; commodity money; Geldpolitik; Gesamtwirtschaftliche Liquidität; Bankenkrise; Politische Gewalt; Dogmengeschichte; USA; Lender of Last Resort